Russia during President Putin's second term : a business and investment review - Terterov, Marat (Global market briefings., 2006)
Researched and written by lawyers and professionals based in the country, this authoritative report considers the latest market reforms and the changes to law and commercial practice in Russia. It covers: recent trends in the Russian investment climate; legal developments and business legislation; changes in the taxation system for 2005-06. It also looks at key trends in Russian business/economic sectors during 2005: energy sector / energy sector legislation; IT and Telecoms; automotive sector; retail; brewing, and at recent mergers and acquisitions. It also includes a special case study: priv.